ANALYSIS OF ACCOUNTING TREATMENT OF GOLD PAWN LOANS AT ISLAMIC BANKS IN PADANGSIDIMPUAN - Nasser Hasibuan, Abdul; Efendi, Sulaiman; Windari, Windari (CV. Radja Publika, 2022)
Accounting is the art of recording, classifying and summarizing events and transactions of a financial nature in an efficient manner and in the form of units of money, and interpreting the results of the process. Accounting as an information system that identifies, records and communicates economic events of an organization to interested parties. Gold pawning is a financing product on the basis of collateral in the form of gold as an alternative to obtain financing quickly. Gold pawn loans are non-refundable loan facilities with gold guarantees with the obligation to borrow at once or in installments within a certain period of time in accordance with the agreement of the lender and the pawner.